Sistem Pendukung Keputusan untuk Seleksi Siswa Berprestasi di SMA Elpida Noelbaki dengan Metode PROMETHEE - Josua Daud Djobo; Aprilya Kana Wadu; Yeri H Djara Djami; Yampi R. Kaesmetan (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
This study aims to develop a Decision Support System (DSS) to facilitate the selection of outstanding students at Elpida Noelbaki High School by applying the PROMETHEE method. This method helps in making decisions efficiently and objectively based on several relevant criteria. The research involves multiple stages, including the collection of achievement criteria data, development of the PROMETHEE model, and implementation of SPK in software form. The PROMETHEE method ranks students based on predetermined criteria, helping to identify those deserving recognition. The results are expected to provide positive contributions to the school and decision-makers by offering a strong and transparent basis for the selection process. Additionally, the implementation of SPK aims to enhance the recognition of students' achievements and motivate them to excel further, both academically and non-academically